(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This study show that instant support, reliability, the focus of customers, the relationship and facilities are the factors contributing to the financial gap. Among these factors, commercial banks’ instant support and installations can increase small and medium businesses’ satisfaction and thus reduce the financial gap. The study also found that manufacturing industry is most affected by financial divide and access to bank finance will support micro, small and medium-sized businesses in India long-term growth and development. The factors leading to the financial gap were statistically negligible from the perspective of commercial banks, risk, NPA, loan costs and knowledge asymmetry. Documentation, slow delivery and feedback on bank lending facilities are not statistically important from a small and medium-sized enterprises point of view. Thus, each sector’s misperceptions of another result from the existence of a financial gap. This led to the lack of demand from small and medium-sized businesses for bank loans. Many of those interviewed, 55 never confronted commercial banks. Better lending options have been available to those businesses that have approached commercial banks. India is regarded as the bank cradle and a good base for industrial growth. Financial inclusion for lending services by small and medium-sized enterprises, division of general banking services by lending services and consideration of determinants identified in the study can reduce the perceptional gap and in the future improve credit flow in this sector. The question of the lack of adequate and timely credit for SMEs therefore needs to be examined. Any study on this question on one side, whether from the point of view of SMEs or from the point of view of commercial banking, would not be complete. It is thus necessary to analyze this problem both in terms of offering commercial banks wide opportunities and in terms of their growth and development, also making a significant contribution to this sector.